1999
DOI: 10.1111/j.2042-3306.1999.tb05265.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on Thoroughbred horses with recurrent exertional rhabdomyolysis performing a standardised exercise test

Abstract: Summary Previous studies have associated recurrent exertional rhabdomyolysis (RER) with a diet high in soluble carbohydrate (CHO). The purpose of this study was to investigate the effect of 3 diets on clinical and metabolic parameters in 5 Thoroughbred horses with RER and 3 healthy Thoroughbreds performing a standardised exercise test (SET). Two diets were formulated to meet energy requirements for the amount of exercise being performed in the form of CHO or fat (21.4 Meal DE/day). The third diet was formulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…The reason for an increased heart rate and/or increased excitability after carbohydrate consumption in horses is not known. MacLeay et al (1999) showed that horses tended to have a higher HR and PCV prior to an exercise test when fed a diet exceeding their energy requirements due to carbohydrate supplementation, compared to when they were fed a fat diet according to their requirements. In addition, in the same study, horses with a history of exertional rhabdomyolysis had significantly higher HRs when fed the excessive diet compared to when fed diets equalling their needs (carbohydrate diet and fat diet).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for an increased heart rate and/or increased excitability after carbohydrate consumption in horses is not known. MacLeay et al (1999) showed that horses tended to have a higher HR and PCV prior to an exercise test when fed a diet exceeding their energy requirements due to carbohydrate supplementation, compared to when they were fed a fat diet according to their requirements. In addition, in the same study, horses with a history of exertional rhabdomyolysis had significantly higher HRs when fed the excessive diet compared to when fed diets equalling their needs (carbohydrate diet and fat diet).…”
Section: Discussionmentioning
confidence: 99%
“…• Overfeeding of carbohydrates (MacLeay et al 1999) • Electrolyte or mineral imbalances, especially with potassium (Harris 1991) • Deficiency of selenium and/or Vitamin E If elite-level performance is to be maintained in horses predisposed to these muscle problems it is crucial to reduce the amount of carbohydrate in the diet as much as possible. This is done by increasing the use of non-starch energy sources such as fibre and oil.…”
Section: Feed-induced Muscle Problemsmentioning
confidence: 99%
“…Performance horses are traditionally fed a starch‐rich, concentrate‐based diet due to the energy requirements for the activities performed in the sport. Nevertheless, this type of diet has been reported to negatively impact the health (Goncalves, Julliand, & Leblond, ; Tinker et al., ; Luthersson, Hou Nielson, Harris, & Parkin, ; MacLeay et al., ) and behaviour (Gillham, Dodman, Shuster, Kream, & Rand, ; Kusunose, ; Redbo, Redbo‐Torstensson, Odberg, Hedendahl, & Holm, ) in the horse, and so, researchers have investigated whether a high‐energy forage‐based diet is detrimental to the performance of the equine athlete (Connysson, Essen‐Gustavsson, Lindberg, & Jansson, ; Connysson et al., ; Essen‐Gustavsson, Connysson, & Jansson, ; Ringmark, Roepstorff, Hedenstrom, Lindholm, & Jansson, ). High‐energy forage‐based diet was reported to be a suitable alternative to a grain‐rich diet in performance horses with benefits documented in the recovery of muscle (Essen‐Gustavsson et al., ) and fluid balance (Connysson et al., ) in the exercising horse along with the overall performance (Ringmark et al., ).…”
Section: Introductionmentioning
confidence: 99%